Animal spirits, investment and unemployment: An old Keynesian view of the Great Recession - Marco Guerrazzi (EconomiA, 2015)
This paper develops a DSGE model with investment and capital accumulation build along demand-driven explanations of the Great Recession. Specifically, following Farmer (2013), I set forth a search framework in which households decide about consumption while firms decide about recruiting effort as well as investment. This setting closed with market clearing in good and asset markets has one less equation than unknowns. As a consequence, in order to solve such an indeterminacy, I assume that investment is driven by self-fulfilling expectations about the adjustment cost of capital. Consistently with the view of business cycles pushed by stock price fluctuations, this model has the potential to provide a more comprehensive rationale for the consumption–investment patterns observed during the years of the crisis. – – O artigo apresenta um modelo DSGE com investimento e acumulaç\~ao de capital para explicar a Grande Recess\~ao pelo lado da demanda. Seguimos Farmer (2013) propondo uma estrutura de search no qual familias decidem o quanto consumir e firmas investem e recrutam m\~ao de obra. Nesse arcabouço há uma equaç\~ao a menos do que incógnitas. De maneira a resolver essa indeterminaç\~ao supomos que o investimento tem expectativas auto-realizáveis sobre o custo de ajustamento do capital. Consistente com a vis\~ao de que os ciclos de negócios s\~ao influenciados pelas flutuaç\~oes dos preços de aç\~oes, esse modelo tem o potencial de prover uma rationale mais compreensiva para os padr\~oes de consumo-investimento observados durante os anos de crise.
Keywords: E24; E32; E52; J64; 330; Investment; Capital accumulation; Finance-induced recession; Search; DSGE models